Ghana : The AIDS Response Project (GARFUND) - Mohan, P. C. (2012)
The specific objectives of this project - financed through an IDA credit of $28.7 million (2002-05) - were to: provide resources that would enable the government to implement a balanced, diversified multi-sector response, engaging all relevant government sectors, non-governmental organizations (NGOs) and grassroots initiatives; to expand contributions made by the Ministry of Health ( MOH ) engage civil society in the fight against AIDS; and finance eligible activities conducted by civil society organizations, including NGOs, community-based organizations (CBOs), faith-based organizations (FBOs), trade and professional associations, associations of people living with HIV/AIDS (PLWHAs), districts, and line ministries to ensure a rapid multisector scaling-up of HIV prevention and care activities in all regions and at all administrative levels.